The epistemological foundations of the Basran grammatical lesson: a reading of the sources of the rationalist approach and its manifestations. - Lazreg , Belabbas (El Omda in Linguistics and Discourse Analysis, 2023)
The grammatical tradition in Basra initially began in a simple form, offering only a superficial description of language. It soon developed into deeper intellectual thinking when grammarians came into contact with external rational disciplines such as philosophy and logic, which are fundamentally based on reason. Consequently, the Basran grammatical school adopted a strong reliance on rational reasoning, which gave it a purely rational orientation. This is clearly reflected in the dominance of analogy, causal explanation, and interpretation within Basran grammatical studies. These thus became the principal epistemological foundations of this tradition.